2007
DOI: 10.1002/jat.1265
|View full text |Cite
|
Sign up to set email alerts
|

Captan: Transition from ‘B2’ to ‘not likely’. How pesticide registrants affected the EPA Cancer Classification Update

Abstract: On 24 November 2004 EPA changed the cancer classification of captan from a 'probable human carcinogen' (Category B2) to 'not likely' when used according to label directions. The new cancer classification considers captan to be a potential carcinogen at prolonged high doses that cause cytotoxicity and regenerative cell hyperplasia. These high doses of captan are many orders of magnitude above those likely to be consumed in the diet, or encountered by individuals in occupational or residential settings. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…The reaction of folpet and thiophosgene with thiol groups in glutathione and proteins Siegel, 1972, 1977;Jernstrom et al, 1993;Liu and Fishbein, 1967;Lukens, 1966;Lukens et al�, 1965;Moriya et al�, 1978;Siegel, 1971aSiegel, , 1971b leads to cytotoxicity and an inflammatory reaction, with a consequent regenerative increase in cell proliferation and ultimately the development of tumors (Figure 7)� The sequence of events involving cytotoxicity and regenerative proliferation is a common mode of action for tumorigenesis by non-DNA-reactive chemicals (Meek et al�, 2003)� Cytotoxicity and regeneration is the same mode of action that has been demonstrated for the duodenal tumors induced in mice by captan (Bernard and Gordon, 2000;Gordon, 2007;2010;US EPA, 2004a)� The mode of action for folpet, including generation of thiophosgene, is similar to that seen with chloroform� Chloroform is metabolically activated to phosgene, which leads to liver and kidney cytotoxicity, regeneration, and ultimately tumors� Like folpet, this is a threshold phenomenon (Andersen et al�, 2000;Meek et al�, 2003)� Thiophosgene is not available systemically based on the chemical reactivity of folpet in the gastrointestinal tract and thiophosgene's rapid degradation in blood, in contrast to the systemic distribution of chloroform and the enzymatic generation of phosgene� In contrast to chloroform, folpet is considerably less toxic, probably related to the rapid extracellular hydrolysis leading to thiophosgene, which must then react with cells, compared to the intracellular generation of phosgene by metabolism of chloroform� Exogenous exposure to phosgene by inhalation, a highly toxic event, is unrelated to the process of the intracellular generation of phosgene from chloroform�…”
Section: Key Eventsmentioning
confidence: 90%
See 1 more Smart Citation
“…The reaction of folpet and thiophosgene with thiol groups in glutathione and proteins Siegel, 1972, 1977;Jernstrom et al, 1993;Liu and Fishbein, 1967;Lukens, 1966;Lukens et al�, 1965;Moriya et al�, 1978;Siegel, 1971aSiegel, , 1971b leads to cytotoxicity and an inflammatory reaction, with a consequent regenerative increase in cell proliferation and ultimately the development of tumors (Figure 7)� The sequence of events involving cytotoxicity and regenerative proliferation is a common mode of action for tumorigenesis by non-DNA-reactive chemicals (Meek et al�, 2003)� Cytotoxicity and regeneration is the same mode of action that has been demonstrated for the duodenal tumors induced in mice by captan (Bernard and Gordon, 2000;Gordon, 2007;2010;US EPA, 2004a)� The mode of action for folpet, including generation of thiophosgene, is similar to that seen with chloroform� Chloroform is metabolically activated to phosgene, which leads to liver and kidney cytotoxicity, regeneration, and ultimately tumors� Like folpet, this is a threshold phenomenon (Andersen et al�, 2000;Meek et al�, 2003)� Thiophosgene is not available systemically based on the chemical reactivity of folpet in the gastrointestinal tract and thiophosgene's rapid degradation in blood, in contrast to the systemic distribution of chloroform and the enzymatic generation of phosgene� In contrast to chloroform, folpet is considerably less toxic, probably related to the rapid extracellular hydrolysis leading to thiophosgene, which must then react with cells, compared to the intracellular generation of phosgene by metabolism of chloroform� Exogenous exposure to phosgene by inhalation, a highly toxic event, is unrelated to the process of the intracellular generation of phosgene from chloroform�…”
Section: Key Eventsmentioning
confidence: 90%
“…Mode of action (MOA) is increasingly being considered in the risk assessment of pesticides� During the past decade, the International Life Sciences Institute (ILSI) and the International Programme on Chemical Safety (IPCS) of the World Health Organization (WHO) have been evolving a framework for the analysis of mode of action for rodent toxicity and carcinogenicity findings along with assessment of their human relevance (Sonich-Mullin et al�, 2001;Meek et al�, 2003;Seed et al�, 2005;Boobis et al�, 2006Boobis et al�, , 2008� Numerous case studies have been published illustrating the applicability of the framework for genotoxic and nongenotoxic cancer modes of action and for cancer and noncancer endpoints� Mode of action analysis has been incorporated into the risk assessment guidelines of various regulatory agencies, including the US Environmental Protection Agency (US EPA, 2005)� Folpet and captan are used for their fungicidal properties in both industrial and agricultural products� Their structures are shown in Figure 1 along with their reaction with thiols� Both compounds have Reregistration Eligibility Decisions (REDs) issued (US EPA 1999a, 1999b as well as subsequent reviews (US EPA 2003, 2004a, 2004b) that included the reclassification of captan from "B2" (probable human carcinogen) to "not likely" at dietary exposures expected from agricultural use (US EPA, 2004a;Gordon, 2007)� The major tumor finding from captan bioassays was gastrointestinal adenomas and adenocarcinomas in mice, primarily in the duodenum� By contrast, there was no carcinogenic effect of captan in rats� The 2004 cancer reclassification was based on the 1999 proposed Carcinogenic Risk Assessment guidelines (US EPA, 1999c) that were finalized in 2005 (US EPA, 2005)� Folpet, chemically and biologically similar to captan, has also been evaluated in rodent carcinogenicity bioassays and has a similar pattern of tumor development, that is, gastrointestinal tumors in mice and the absence of treatmentrelated tumors in rats� Studies evaluating the early stages of effects in the gastrointestinal tract support analysis of the mode of action� Folpet provides an example of how the application of the ILSI/IPCS mode of action and human relevance framework can be applied to tumors in assessing possible carcinogenic risk to humans� Folpet previously was considered by EPA a genotoxic carcinogen, like captan, and was considered a carcinogen in mice and rats (Quest et al�, 1993)� Given the information available concerning mode of action, assessment of human relevance and the precedent setting case of captan, folpet today would likely be classified as a nongenotoxic, threshold-based carcinogen, with carcinogenicity only in mice� We describe below the basis for concluding that the rat bioassays are negative; this has also been the conclusion of Joint Food and Agriculture Organization of the United Nations (FAO/WHO) Meeting on Pesticide Residues (JMPR) (FAO/WHO, 1996) and European Food Safety Au...…”
Section: Introductionmentioning
confidence: 99%
“…As such, the RfD of 0.003 mg kg −1  day −1 is protective against both intestinal wounding and intestinal carcinogenesis induced by Cr(VI). Such threshold‐based toxicity criteria have been developed for the SI carcinogens captan and folpet based on evidence for a similar MOA involving intestinal wounding and chronic regenerative hyperplasia (EFSA, 2009; Gordon, 2007; US EPA, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…However, upon subsequent agency review following an appeal by the industryaffiliated Captan Task Force and review by an independent expert group, the agency concluded that that ''captan acts through a nongenotoxic threshold mode of action'' [32,33]. The agency accepted the MOA proposed by Captan Task Force that ''captan induces adenomas and adenocarcinomas in the duodenum of the mouse by a non-genotoxic MOA involving cytotoxicity and regenerative cell hyperplasia that exhibits a clear dose threshold.…”
Section: Examples Of Mutagenic Mode Of Action Determinationsmentioning
confidence: 98%